2000
DOI: 10.1159/000053871
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Confined Placental Mosaicism with Fetal Intrauterine Growth Retardation

Abstract: Objective: Our purpose was to determine if the frequency of confined placental mosaicism in newborns with unexplained intrauterine growth retardation (IUGR) was higher compared with infants with appropriate growth in utero and the outcome of these pregnancies. Study Design: A total of 20 cases with unexplained IUGR and 20 cases with appropriate growth for gestational age has been studied. Amnion, chorion and villi biopsy specimens were obtained from growth-retarded cases and controls at delivery. Cord blood sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…There were three infants with RSS (one of CPM group and two of non-CPM group). Patient 2, who had CPM for del(2)(p16), showed normal developmental performance and [Wolstenholme et al, 1994] and a stillbirth with CPM for del(16)(p16) [Stipoljev et al, 2001]. Our infant with CPM for del(2)(p16) is added to the list of CPM for partial monosomy that may cause IUGR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There were three infants with RSS (one of CPM group and two of non-CPM group). Patient 2, who had CPM for del(2)(p16), showed normal developmental performance and [Wolstenholme et al, 1994] and a stillbirth with CPM for del(16)(p16) [Stipoljev et al, 2001]. Our infant with CPM for del(2)(p16) is added to the list of CPM for partial monosomy that may cause IUGR.…”
Section: Discussionmentioning
confidence: 97%
“…The correlation between CPM and intrauterine growth restriction (IUGR) of infants has remained controversial. Some studies showed higher frequency (6.5%-25%) of IUGR in pregnancies with CPM than those (5.0%-8.3%) in those without CPM [Kalousek et al, 1991;Ledbetter et al, 1992;Kalousek, 1994;Wolstenholme et al, 1994;Artan et al, 1995;Wilkins-Haug et al, 1995;Krishnamoorthy et al, 1995;Stipoljev et al, 2001], whereas others gave negative association between IUGR and CPM [Schwinger et al, 1989;Kennerknecht et al, 1993]. When trisomy rescue occurs ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of CPM in the general population affected by IUGR is roughly ten times higher than in pregnancies with a normal outcome (Table IV). However, the incidence of CPM in the general population in association with congenital abnormalities is hard to estimate because the study of CPM in such cases is often not undertaken [Kennerknecht et al, 1993;Stipolijev et al, 2001]. The rate of CPM in the ICSI population, a population which may be at a higher risk for being affected by CPM, is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal injuries in cases of mesenchymal dysplasia are well reported and it is known that about 1-2% of this change, often unsuspected, is associated with placental mosaicism [25].…”
Section: Placental Pathological Features and Adverse Fetal Outcomementioning
confidence: 99%
“…Both cord's pathology and pathology related to the presence of VA are well documented and understood. Secondary vasculogenic organ damage and destructive lesions can occur in the survivor after fetal death of one twin, particularly in monochorionic twins, while polyhydramnios and oligohydramnios are most frequently found in chronic TTTS and yet justify the discrepancy of fetal growth [25].…”
Section: Placental Pathological Features and Adverse Fetal Outcomementioning
confidence: 99%